Educational values in the poetry of (Al-Mahwi), with tolerance as a model. - Ghafar, Dr. Jalal Jamal Ghafar; Mustafa, Dr. Umid Mohammed Amin Mustafa (Sulaimani Journal for Humanities, 2026)
This abstract examines tolerance in Al-Mahwi’s poetry, merging literary and educational perspectives. He promotes forgiveness over revenge, seeing tolerance as key to social harmony. Acknowledging his flaws, he seeks pardon from others and God, reflecting spiritual depth. His work emphasizes that true tolerance stems from self-awareness and divine mercy. This dual focus on human and spiritual forgiveness reveals the ethical richness of his poetry, offering insights for academic discourse. Al-Mahwi’s call for tolerance remains a timeless appeal for reconciliation and peace.